Diversity of Arbuscular Mycorrhizal Fungi Associated with Medicinally Important and Natural Dye Yielding Plant (Indigofera tinctoria, L.) from Kanyakumari District, Tamil Nadu - Sundar, S. K.; Palavesam, A.; Mohan, V.; Parthipan, B. (Indian Forester, 2011)
In the present study, an attempt was made to investigate the status of AM fungal association and the physico-chemical properties of the rhizosphere soil of an important medicinal plant,Indigofera tinctoria from three different localities of Kanyakumari District, Tamil Nadu. The physico-chemical analysis showed that the soil was slightly acidic to neutral pH. The nutrient status was found to be low to moderate in nature. The diversity of AM fungal species was also investigated and it was observed that the plant was positive for AM association and has distinct pattern of AM fungal diversity with 15 different AM fungal species of four genera in the three sites studied. Among them, the genus Glomus was the dominant one. Trap culture study was conducted to isolate AM fungal spores which showed presence of two additional AM fungal species. The species richness, diversity indices, colonization percentage and spore numbers of AM fungi were higher in Vell hills region followed by other two sites.